ANALISIS RELEVANSI PENERAPAN AKUNTANSI DANA PADA AKUNTANSI PEMERINTAH INDONESIA - Sugiyanto, Hari (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2019)
The Indonesian government has applied the accrual basis in preparing its financial statements. However, it is possible to implement fund accounting. In the PP Conceptual Framework Number 71 Year 2010 it is stated that the Indonesian government can apply fund accounting for control purposes. Fund Accounting is an accounting system that is often used by non-profit organizations and public sector institutions, including government. The system is a method of recording and displaying entities in accounting such as assets and liabilities which are grouped according to their respective uses.This study aims to determine the relevance of the application of fund accounting in Indonesia and conduct a literature study on fund accounting practices in the United States government.Although the Indonesian government has applied accrual-based accounting, it does not rule out the possibility that fund accounting will be applied. Of course the authorized entity needs to draw up relevant regulations so that the accounting of funds is relevant to the implementation of accrual-based government accounting.